ECO-PESANTREN AS THE PANACEA FOR GLOBAL CLIMATE CHANGE: LESSONS FROM NURUL HARAMAIN NW LOMBOK ISLAMIC BOARDING SCHOOL INDONESIA - Abdul Quddus (Universitas Islam Negeri (UIN) Mataram, 2020)
This paper examined the ecological concept and its implication at Nurul Haramain NW Lombok Islamic boarding school in response to the world climate crisis. Boarding schools have the potentials to bridge the environmental conservation initiative amid the secular science phenomena. This study employed a descriptive-explorative approach using a qualitative methodology. Thus, theoretically, this study was anchored in Mary Evelyn Tucker and Vasudha Narayan's theories of eco-theology in addressing the climate crisis. The findings showed that Nurul Haramain NW Lombok Islamic boarding school had implemented a sustainable lifestyle based on the ecological values in the Al-Quran and Hadith, in which Tuan Guru as the environmental conservation foreman. Keywords: Eco-Pesantren, Climate Change, Environmental Crisis, Educational Theology, Eco Theology